Analisis Etnopedagogik Pada Kasepuhan Cipta Gelar Di Banten Tradisi Ngabungbang - Setiani, Henny; Hidayat, Sholeh; Leksono, Suroso Mukti; Jamaudin, Ujang (Literasi: Jurnal Ilmu Pendidikan, 2023)
This study aims to find out the Ethno-Pedagogic aspect of a Ngulungbang Tradition in Kasepuhan Cipta Prestasi. This research uses qualitative and uses literature and field analysis to obtain data. The results of the study show that the ethno-pedagogic aspects found are at a stage of the Ngulungbang Tradition, namely bathing at night. The analyzed night bath does not cause rheumatism but nourishes the body. The view of the local people who think that bathing causes arthritis is a mistake that can be straightened out in the end.